Functional Results of Limb Salvage in Below-Knee Type III C Open Fractures or Traumatic Amputations - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2012)
This study presents the surgical and functional outcomes of below-knee total leg amputation and Gustilo type III C open fracture cases that were considered appropriate for salvage treatment according to a more proactive approach, despite being candidates for amputation according to the current scoring systems. Nineteen patients (21 legs) underwent replantation-revascularization surgery. At least Chen Grade II functional level was the aim. A limb salvage operation was performed in 21 legs in 19 patients (18 male, 1 female). The mean age was 28.5 years (range: 11 to 42 years). Six legs in four patients presented with total amputation, and 15 legs in 15 patients had Gustilo Type III C open fractures. A successful replantation/revascularization was performed in 20 legs, with a Chen Grade I and Grade II functional outcome in 3 and 17 legs, respectively. None of these patients were eligible for salvage operation according to currently used scoring systems. Limb-preserving surgery performed upon the assessment of local and general conditions of the patients with traumatic below-knee amputations or Gustilo Type III C open fractures seems to be a viable therapeutic option that can serve to achieve Chen Grade II functional level in most patients.
Keywords: total leg amputation; Gustilo type III C open fracture; limb salvage; OPEN TIBIAL FRACTURES; LOWER-EXTREMITY TRAUMA; MANGLED EXTREMITY; INJURY; MANAGEMENT; UTILITY; SYSTEM; INDEX